2012
DOI: 10.1590/s1676-06032012000300002
|View full text |Cite
|
Sign up to set email alerts
|

Reptiles of the municipality of Juiz de Fora, Minas Gerais state, Brazil

Abstract: Abstract:The Atlantic Forest of the state of Minas Gerais, as well as the remnants of this domain in the rest of Brazil, suffers a marked reduction in size and anthropogenic alteration. This habitat degradation is directly reflected in the decrease of species richness within these natural environments. In this sense, the inventory of extant species is necessary to understand the species composition of regions under threat. Despite the great richness of existing reptile species in Minas Gerais, the level of kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
6
1
1
Order By: Relevance
“…UPGMA cluster method and Jaccard's dissimilarity index. 1-Serra do Ouro Branco (this study), 2-EPDA Peti(Bertoluci et al 2009), 3-Viçosa(Costa et al 2009), 4-Serra do Brigadeiro(Moura et al 2012), 5-Juiz de Fora(Sousa et al 2012), 6-Ritápolis (Sousa et al 2010), 7-Parque Nacional Grande Sertão Veredas (Recorder and Nogueira 2007), 8-Reserva Ecológica Unilavras-Boqueirão (Novelli et al 2012), 9-Lagoa Santa (Reinhardt and Lutken 1861), 10-Nordeste de Minas Gerais (Feio and Caramaschi 2002), 11-Instituto Inhotim (Linares and Eterovick 2013).…”
mentioning
confidence: 85%
“…UPGMA cluster method and Jaccard's dissimilarity index. 1-Serra do Ouro Branco (this study), 2-EPDA Peti(Bertoluci et al 2009), 3-Viçosa(Costa et al 2009), 4-Serra do Brigadeiro(Moura et al 2012), 5-Juiz de Fora(Sousa et al 2012), 6-Ritápolis (Sousa et al 2010), 7-Parque Nacional Grande Sertão Veredas (Recorder and Nogueira 2007), 8-Reserva Ecológica Unilavras-Boqueirão (Novelli et al 2012), 9-Lagoa Santa (Reinhardt and Lutken 1861), 10-Nordeste de Minas Gerais (Feio and Caramaschi 2002), 11-Instituto Inhotim (Linares and Eterovick 2013).…”
mentioning
confidence: 85%
“…Many reptile species found in this study are frequently associated with anthropogenic habitats, such as the exotic gekkonid Hemidactylus mabouia and the native lizards Ameiva ameiva, Cercosaura ocellata, Iguana iguana, Tropidurus oreadicus, as well as the snakes Boa constrictor, Epicrates crassus, Chironius flavolineatus, Sibynomorphus mikanii, and Oxyrhopus trigeminus (Carvalho & Nogueira 1998;Sousa et al 2012;França & Braz 2013). Nevertheless, some species depend on remnants of pristine habitats, such as the fossorial reptiles Amphisbaena anaemariae, Anilius scytale, and Trilepida fuliginosa, reinforcing the importance of the recovering areas in the maintenance of local reptile diversity.…”
Section: Discussionmentioning
confidence: 95%
“…The lizard and amphisbaenian species richness of Cataguases represents 16% of the known diversity of these groups in the state of Minas Gerais (H. C. Costa, unpublished data). Most species have wide geographical ranges and are commonly found in habitats with human interference like forests patches in urban areas (e.g., Costa et al 2009, Moura et al 2012, Sousa et al 2012, Cruz et al 2014. Only three species (Ecpleopus gaudichaudii, Enyalius boulengeri, and Gymnodactylus darwinii, 20% of observed richness) are considered endemic to the Atlantic Forest.…”
Section: Discussionmentioning
confidence: 99%
“…Herpetological assessments are recent in the 'Zona da Mata' (e.g., Costa et al 2009, Moura et al 2012, Sousa et al 2012, and have revealed high species richness and even new taxa (e.g., Lacerda et al 2012, Santana et al 2012, Assis et al 2013, Guimarães et al 2017. Besides increasing the knowledge of biodiversity, inventories are fundamental for conservation plans (Haddad 1998) and provide a set of valuable information for ecology (Droege et al 1998) and macroecology (Moura et al 2016).…”
Section: Introductionmentioning
confidence: 99%